1999
DOI: 10.1128/iai.67.9.4307-4311.1999
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Pyrogenic Exotoxin F (SpeF) Causes Permeabilization of Lung Blood Vessels

Abstract: Acute respiration distress syndrome (ARDS) is a typical complication in toxic shock-like syndrome (TSLS) caused byStreptococcus pyogenes. An isolated perfused rat lung model was used to identify the causative agent of ARDS in TSLS in this study. Some crude preparations separated from the culture supernatants ofS. pyogenes isolates caused rapid increases in the weight of perfused lungs, indicating vascular permeabilization. Six samples from M type 1 and 3 isolates from TSLS and pharyngitis patients showed stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…SpeB can promote the spread of bacteria and their products in host tissues by degrading the tissue structure and can also degrade proteins and antimicrobial peptide LL-37 in order to resist immunity ( Walker et al, 2014 ). SpeF is the main cause of pulmonary vascular permeability, which is sufficient to cause acute respiratory distress syndrome under the conditions of toxic shock-like syndrome caused by S. pyogenes ( Matsumoto et al, 1999 ). Among all virulence factors, SAg is of particular concern.…”
Section: Discussionmentioning
confidence: 99%
“…SpeB can promote the spread of bacteria and their products in host tissues by degrading the tissue structure and can also degrade proteins and antimicrobial peptide LL-37 in order to resist immunity ( Walker et al, 2014 ). SpeF is the main cause of pulmonary vascular permeability, which is sufficient to cause acute respiratory distress syndrome under the conditions of toxic shock-like syndrome caused by S. pyogenes ( Matsumoto et al, 1999 ). Among all virulence factors, SAg is of particular concern.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that they help bacterial spreading by liquefying pus (Tillet et al ., 1948) and that, being mostly phage‐encoded, they may help the induced phages to digest the DNA released during bacterial lysis (Broudy et al ., 2002). One of the best‐characterized streptodornases, DNase B (also known as mitogenic factor, MF, or SpeF), causes permeabilization of lung blood vessels as a complication of toxic shock‐like syndrome (Matsumoto et al ., 1999). Besides DNase B, four GAS proteins with DNase activity have been identified: streptodornase D (SdaD) (Podbielski et al ., 1996), Sdα (Hasegawa et al ., 2002a), mitogenic factor 2 (MF2) or Spd1 (Broudy et al ., 2002), and mitogenic factor 3 (MF3) or Spd3 (Hasegawa et al ., 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by western blot analysis with DNase Bspecific antibodies. Western blot analysis was performed as described previously (4) and band intensity of the DNase B protein was measured by an ImageMaster Labscan version 3.00 (Amersham Biosciences Corp., Piscataway, N.J., U.S.A.). DNase B proteins were detected at similar levels of amount in the culture of these strains except the DNase B3 strain (Fig.…”
Section: C57 C78mentioning
confidence: 99%
“…of strains) sdaB allele (No. of strains) 1 (9) sdaB6 (9) 2 (8) sdaB7 (8) 3 (7) sdaB2 (7) 4 (8) sdaB7 (8) 6 (8) sdaB1 (8) 11 (5) sdaB3 (1) sdaB8 (4) 12 (7) sdaB9 (7) 18 (5) sdaB10 (5) 22 (6) sdaB11 (6) 28 (7) sdaB4 (1) sdaB12 (6) 50/62 (1) sdaB13 (1) 87 (1) sdaB5 (1) 89 (5) sdaB14 (5) 94 (6) sdaB15 (6) (83) The protein preparations precipitated with final 10% trichloroacetic acid from each volume of the culture supernatant shown in the left side were subjected to SDS-PAGE and then blotted onto a nitrocellulose membrane and detected with the anti-DNase B serum as described previously (4). Lanes 1 to 3: the protein preparations from emm3 strains with DNase B2, respectively; Lane 4: the protein preparation from an emm11 strain with DNase B3; Lane 5: the protein preparation from an emm28 strain with DNase B4.…”
mentioning
confidence: 99%